Geographic distribution, genetic variability and biological properties of rice orange leaf phytoplasma in Southeast Asia - Ong, Socheath; Jonson, Gilda B.; Calassanzio, Matteo; Rin, Soriya; Chou, Cheythyrith; Oi, Takao; Sato, Ikuo; Takemoto, Daigo; Tanaka, Toshiharu; Choi, Il-Ryong; Nign, Chhay; Chiba, Sotaro (MDPI, 2021)
Rice orange leaf phytoplasma (ROLP) causes clear orange to yellowish leaf discoloration and severe stunting in rice seedlings. The ecological and biological characteristics of ROLP are largely unknown because the disease has not widely caused serious problems in rice cultivated areas, thereby leading to the low accumulation of research data. However, in the past decade, the disease became a threat to rice production, particularly in South China and India; it has also been recognised in other Asian countries, such as Vietnam, Thailand and the Philippines. Here, we observed the occurrence of ROLP in paddies of the Southeast Asian counties (Cambodia, Vietnam and the Philippines) and found that the isolates in the Philippines and Vietnam were monophyletic, while those in India, Thailand and Cambodia were more diverse, suggesting their potential origins. In Cambodia, it was revealed that following polymerase chain reaction (PCR) detection, the known ROLP-insect vectors, N. virescens Distant and Recilia dorsalis Motchulsky, were ROLP-positive, indicating their roles in pathogen dispersal. Moreover, fluorescent and scanning electron microscopy revealed the intensive accumulation of the phytoplasma in phloem tissues and massive accumulation of storage starch in vascular bundle sheath and parenchyma. Altogether, this study illustrated the genetic variability of global ROLP isolates and the pathogen’s biological impact on rice tissue.